Genetic Relations Between Effortful and Attentional Control and Symptoms of Psychopathology in Middle Childhood - Lemery-Chalfant, Kathryn (Infant Child Dev, 2008)
Elucidating the genetic and environmental etiology of effortful control (mother and father report at two time points), attentional control (observer reports) and their associations with internalizing and externalizing symptoms (mother and father report) is the central focus of this paper. With a sample of twins in middle childhood participating in the Wisconsin Twin Project, broad sense heritability for parental report effortful control ranged from 68–79%, with a slightly higher heritability estimate of 83% for observer report attentional control, and no influence of the shared environment on either trait. Further, measures of control were negatively correlated with internalizing and externalizing symptoms longitudinally, concurrently, and across reporters. Importantly, shared additive genetic influence accounted for the covariation between the control variables and symptoms of psychopathology. These results encourage identification of common genes that affect both effortful control and symptoms, and environmental triggers that uniquely influence symptoms of psychopathology.